2020
DOI: 10.1002/ajh.25780
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of micro‐transplantation from HLA fully mismatched unrelated and partly matched related donors in acute myeloid leukemia

Abstract: Micro‐transplantation (MST) by chemotherapy, combined with granulocyte colony‐stimulating factor‐mobilized peripheral blood stem cell (GPBSC) infusion, from an HLA partial matched related donor has shown some encouraging effective therapy for acute myeloid leukemia (AML). However, the outcome of human leukocyte antigen (HLA) fully mismatched unrelated donor‐derived MST in such patients is still unknown. In the present study, we compared the efficacy of HLA fully mismatched unrelated donor‐derived MST, and part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Importantly, the induced host tumor-specific CTLs persisted long-term in vivo to protect against tumor recurrence. Collectively, data from our studies and others [71][72][73][74] indicate that allogeneic cells have the potential to induce host anti-tumor immunity and may induce long-term protection against both solid tumors and AML.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Importantly, the induced host tumor-specific CTLs persisted long-term in vivo to protect against tumor recurrence. Collectively, data from our studies and others [71][72][73][74] indicate that allogeneic cells have the potential to induce host anti-tumor immunity and may induce long-term protection against both solid tumors and AML.…”
Section: Discussionsupporting
confidence: 60%
“…Recent clinical studies have demonstrated that HLAmismatched granulocyte colony-stimulating factor-mobilized donor peripheral blood stem cell (G-PBSC) infusion after regular chemotherapy improves the outcome in elderly patients with acute myeloid leukemia (AML) [71][72][73][74]. Although the recipients did not receive any GVHD prophylaxis, GVHD was rarely observed.…”
Section: Discussionmentioning
confidence: 99%
“…MST is an important treatment for patients who cannot tolerate standard allo-HSCT or lack suitable donors (2)(3)(4)(5)(6). Donor selection for MST is broad, ranging from HLA fully mismatched unrelated donors to HLA partly matched related donors and the efficacy of unrelated donor-derived MST is believed to be similar to or higher than that of related donorderived MST (2,3). HLA haplotype homozygous donors have been reported to cause fatal transfusion-associated GVHD when patients receive a transfusion of nonirradiated blood components as early as 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Infusion of HLA-mismatched donor granulocyte colony-stimulating factor (G-CSF) mobilized peripheral blood stem cells (G-PBSCs) combined with chemotherapy (microtransplantation [MST]) is capable of producing donor microchimerism (donor cells<1%), improving survival, and precluding GVHD (2). It's a safe and effective treatment for older patients with AML (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ai Huisheng et al (6,(12)(13)(14) explored the application of "micro-transplantation" to treat several hematological malignancies, included MDS, AML, and Philadelphia chromosome-positive acute lymphoblastic leukemia. The (7).…”
Section: Discussionmentioning
confidence: 99%